31.3k views
1 vote
What is a solution to the equation 3 / m + 3 - M / 3 - M equals m^2 + 9 / m^2-9?​

What is a solution to the equation 3 / m + 3 - M / 3 - M equals m^2 + 9 / m^2-9?​-example-1
User Phq
by
5.1k points

1 Answer

6 votes

Answer: Last option.

Explanation:

Given the equation:


(3)/(m+3)-(m)/(3-m)=(m^2+9)/(m^2-9)

Follow these steps to solve it:

- Subtract the fractions on the left side of the equation:


(3(3-m)-m(m+3))/((m+3)(3-m))=(m^2+9)/(m^2-9)\\\\(9-3m-m^2-3m)/((m+3)(3-m))=(m^2+9)/(m^2-9)\\\\(-m^2-6m+9)/((m+3)(3-m))=(m^2+9)/(m^2-9)

- Using the Difference of squares formula (
a^2-b^2=(a+b)(a-b)) we can simplify the denominator of the right side of the equation:


(-m^2-6m+9)/((m+3)(3-m))=(m^2+9)/((m+3)(m-3))

- Multiply both sides of the equation by
(m+3)(3-m) and simplify:


((-m^2-6m+9)(m+3)(3-m))/((m+3)(3-m))=((m^2+9)(m+3)(3-m))/((m+3)(m-3))\\\\-m^2-6m+9=((m^2+9)(3-m))/((m-3))

- Multiply both sides by
m-3:


(-m^2-6m+9)(m-3)=((m^2+9)(3-m)(m-3))/((m-3))\\\\(-m^2-6m+9)(m-3)=(m^2+9)(3-m)

- Apply Distributive property and simplify:


(-m^2-6m+9)(m-3)=(m^2+9)(3-m)\\\\-m^3-6m^2+9m+3m^2+18m-27=3m^2+27-m^3-9m\\\\-m^3-3m^2+27m-27+m^3-3m^2+9m-27=0\\\\-6m^2+36m-54=0

- Divide both sides of the equation by -6:


(-6m^2+36m-54)/(-6)=(0)/(-6)\\\\m^2-6m+9=0

- Factor the equation and solve for "m":


(m-3)^2=0\\\\m=3

In order to verify it, you must substitute
m=3 into the equation and solve it:


(3)/(3+3)-(3)/(3-3)=(3^2+9)/(3^2-9)\\\\(3)/(6)-(3)/(0)=(18)/(0)

NO SOLUTION

User JenyaKh
by
4.4k points